(untitled) (New York, 2002)
Aquaculture for both finfish and shellfish is expanding rapidly throughout the world. It is regarded as having the potential to provide a valuable source of protein in less developed countries and to be integrated into the farming systems and livelihoods of the rural poor. This book addresses key issues in aquaculture and rural development, with case studies drawn from several countries in South and South-East Asia. Papers included cover topics ranging from production and technical issues (such as pond culture and rice field fisheries) to social aspects and research and development methodology. The book has been developed from a meeting of the Asian Fisheries Society. It is aimed at all concerned with aquaculture and rural development.
Keywords: Aquaculture; Congresses; Asia, Southeastern